Profile of Potential Drug Interactions in Chronic Obstructive Pulmonary Disease Patients in One of the Jember District Hospitals - Dea Agita Anggraini; Shinta Mayasari (Jurnal EduHealth, 2026)
Background: Chronic Obstructive Pulmonary Disease or often abbreviated as COPD is a term used for a number of non-communicable diseases that affect the lungs for the long term. COPD is the third leading cause of death in the world. The use of drugs in COPD patients with or without comorbidities is included in the category of drug use with more than two drug items, resulting in one of the DRPs, one of which is drug interaction. The prevalence of patients with potential drug interactions in Ethiopian hospitals was found to be 72.2%. The number of COPD cases is projected to increase by 112 million to a total of 592 million by 2050 (9.5% of the total eligible population), a relative increase of 23.3% from 2020 to 2050. Purpose: The purpose of this study was to determine the study of drug interactions in patients with Chronic Obstructive Pulmonary Disease at the Jember Pulmonary Hospital. Methods: This type of research is qualitative research using the observation method, retrospective data collection taken from medical record data of COPD patients. The number of samples in this study was 96 patients calculated using the Slovin formula. The sampling technique used was random sampling technique. Data were processed using Microsoft Excel and displayed in the form of frequencies and percentages. Conclusion: Potential drug interactions in COPD patients that occurred in one of the Jember Regency hospitals amounted to 97.92% using drug interaction checker with details of minor interaction categories 26,48%, moderate 68,80% and major 4,72%. Monitoring the occurrence of potential drug interactions is carried out in order to minimize the risk of drug side effects. Complaints of potential interactions in patients do not occur which can be seen from clinical manifestations in patients. The limitation of this study is that it does not know the patient's complaints directly because it only uses medical record data.